PRACTICAL APPLICATION OF SIX SIGMA METHODOLOGY TO REDUCE DEFECTS IN A PAKISTANI MANUFACTURING COMPANY - Wassan, Rano Khan; Hulio, Zahid Hussain; Gopang, Miskeen Ali; Memon, Umair Sarwar; Ali Akbar; Shuaib Kaka (Journal of Applied Engineering Science, 2022)
All over the world six sigma is being adopted as a quality improvement approach towards zero defects. Unfortunately, the adoption of the six sigma methodology in manufacturing companies is very rare in developing countries due to different challenges and Pakistan is standing in the same row. This article demonstrates the practical use of various six sigma tools throughout Define, Measure, Analyze, Improve and Control (DMAIC) cycle by conducting a case study of manufacturing company in Pakistan. The potential problem was the external leakage defect in refrigerator during its production. The goal of this project was to identify critical root causes of external leakage and eliminate them with the help of six sigma DMAIC methodology. Project charter, Pie chart, Bar chart of faults, Suppliers Input Process Output (SIPOC), Voice of Customer (VOC) and flow process map were used to define the problem, its scope and process routing. Pareto chart was used to identify sub defects and sigma level was calculated for the existing process. Feed rate, capillary action of filler material, cleanliness, visual inspection and unsuitable heat input were the major causes of external leakage, identified by cause and effect diagram. Cause and effect matrix was developed to rank the identified causes. Further, DoE was performed to improve the process by conducting different alterations in the parameters. In order to control the process, FMEA sheet was prepared to sustain the process improvements. The FMEA control plan needed to be revised at specific time intervals to attain continuous process improvement. External leakage defect was reduced by 30% and service call rate (SCR) was improved with lower complaints from customers.